PENDEKATAN PEER TEACHING BERBENTUK GROUP DISCUSSION UNTUK MENINGKATKAN PEMBELAJARAN DHAMIR DI KELAS X-1 MAN KOTA SURABAYA - Intan Safitri (Unit Pengembangan Bahasa UIN Sayyid Ali Rahmatullah Tulungagung, 2022)
Peer teaching or commonly referred to as peer tutoring is a method based on student activity in learning. Certain students who meet the criteria will be appointed by the teacher to become tutors and teach their friends in a group. So that the material delivered by peer tutors will be understood by each student in the group equally. This study aims to determine the effect of applying the peer teaching method with a group discussion strategy to improve understanding of nahwu rules. This research uses a qualitative approach with the type of case study. Data collection techniques in this study were using observation and tests. The population in this study were all students of class X MAN Surabaya, while the sample in this study were students of class X-1, totaling 34 students. Based on the results of the study, it can be concluded that the peer teaching method with a group discussion strategy has a positive influence on increasing the understanding of nahwu rules in class X-1 students of MAN Surabaya City.